Pelatihan Kewirausahaan Digital Platform Tiktok Untuk Menumbuhkan Jiwa Minat Berwirausaha Siswa SMAN 9 Kota Bengkulu - Saharani, Dea; Astuty, Kamelia; Hanila, Siti; Sudarsono, Aji (Jurnal Gotong Royong, 2024)
This Community Service Activity is entitled "Digital Entrepreneurship Training on the Tiktok Platform to Cultivate the Entrepreneurial Spirit of Students of SMK Negeri 1 Bengkulu City" which involves students of SMA Negeri 9. This activity is carried out with the aim of providing knowledge and training about Digital Entrepreneurship where development Digital technology opens up new opportunities for entrepreneurs, including students of SMA Negeri 9 Bengkulu City. However, the lack of skills and even education means that there are still many obstacles when you want to start a business. This activity contains material as well as discussions and even a question and answer system between SMA Negeri 9 students and the presenters so that they can have an understanding of digital entrepreneurship. The results of this activity show that digital entrepreneurship training is very effective in increasing the entrepreneurial interest of vocational school students and students. It is hoped that students can develop interests and skills to start a business through technological advances and be ready to face business opportunities in the digital era